2017
DOI: 10.1111/jdv.14220
|View full text |Cite
|
Sign up to set email alerts
|

Acquired perforating dermatosis: clinicopathological study of 31 cases, emphasizing pathogenesis and treatment

Abstract: Acquired perforating dermatosis is an underdiagnosed dermatosis frequently associated with systemic disorders. Its pathogenesis may involve vascular damage, not only in patients with diabetes, but also in those with arterial hypertension and chronic venous insufficiency. Control of pruritus and underlying extracutaneous disorders, as well as discontinuation of the treatment with biologics, are important aspects of the management of this dermatosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
94
5
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(104 citation statements)
references
References 40 publications
3
94
5
2
Order By: Relevance
“…The main cause of CKD was diabetic nephropathy, as in previous studies . Contrasting with other series, only 37.5% of the patients with CKD were receiving kidney replacement therapy . Although APD is scarcely reported in association with solid organ transplant, George et al reported a prevalence of 2.7% in a series of kidney transplant recipients .…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…The main cause of CKD was diabetic nephropathy, as in previous studies . Contrasting with other series, only 37.5% of the patients with CKD were receiving kidney replacement therapy . Although APD is scarcely reported in association with solid organ transplant, George et al reported a prevalence of 2.7% in a series of kidney transplant recipients .…”
Section: Discussionmentioning
confidence: 68%
“…Although hypertension and cardiovascular diseases were frequent comorbidities in this study, we hypothesize that these disorders were not the dominant factor implicated in the development of APD, given its high prevalence on overall population and the fact that almost all of the patients presented other underlying systemic diseases, in particular DM and CKD. However, García‐Malinis et al proposed that vasculopathy underlying chronic venous insufficiency and hypertension might be involved in the pathogenesis of APD …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Advanced glycosylation end products in diabetes alter the differentiation of epidermal and dermal components leading to their transepidermal elimination 2. Diabetes-induced microangiopathy and dialysis-related microdeposition of exogenous agents may predispose to the APD 3. There are reports of improvement of skin lesions with the management of the underlying disorder 3.…”
mentioning
confidence: 99%
“…Diabetes-induced microangiopathy and dialysis-related microdeposition of exogenous agents may predispose to the APD 3. There are reports of improvement of skin lesions with the management of the underlying disorder 3. Topical steroids, retinoids and oral antihistamines are prescribed for localised lesions.…”
mentioning
confidence: 99%